Supply Chain Risk Management in International Trade Operations Between Germany and Brazil - Meike Schroeder; Renato Barata Gomes (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
While different aspects of export barriers and supply chain risks in companies have been discussed in literature intensively, there exist only a small number of current, international studies analyzing supply chain risks that might occur in companies during international trade operations between Germany and Brazil. Thus, the aim of this paper is to identify and classify potential risks that might occur during international trade operations between German and Brazilian companies compromising the supply chain management. Moreover, supply chain risk management measures will be compiled to support entrepreneurs in managing those risks. In the remainder of the paper, at first the theoretical background is provided for risk and supply chain risk management. Afterwards, a literature review of existing studies related to export problems is given and the research methodology for the empirical part is described. Subsequently, the empirical results of expert interviews, that have been conducted so far, reflect the work in progress. In addition, first developed measures are presented regarding operational risks. Finally, the paper finishes with a conclusion and further research.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; Supply chain risk management; Brazil; Germany; international trade